Pendidikan Literasi Media Pada Guru Tk Gugus Kasunanan sebagai Upaya Menanggulangi Dampak Negatif Televisi - Triyono, Agus (WARTA, 2010)
Television as part of the development of technology has been able to change the wayhuman life ranging from how to speak, dress, etc. chivalry ethics. Reality is there thecommunity is very far from what is called intelligent concept of media. Many parentswho do not pay attention to media consumption by their children and how muchimpact negetif raised by TV. Efforts to revive awareness of members of the Society ofTeachers Kindergarten Cluster Mangkunegaran about the negative influence of TVwith the concept of media literacy is expected to be applied in everyday life, has beenable to open the horizons of thought participants to the impact of TV. Critical attitudetoward TV has begun to take shape that comes to the end they hope to have a realaction from the government to fix the TV programs in Indonesia.